Formation of the USA foreign policy strategy in the aftermath of World War II: the analysis of factors and goals that shaped the reality today - Plashchinsky, Alexander A. (Journal of the Belarusian State University. Sociology, 2020)
The article views the process of formation of the USA foreign policy strategy as being an instrument of establishing a new world order in the aftermath of World War II. An array of information, which consists of numerous sources in English, has been introduced into the scientific circulation of Belarusian political science and translated by the author himself. These are USA foreign policy documents, archival materials, memoirs, specialised periodicals, etc. Based on system analysis of this information, the key factors that determined the formation of the USA global strategy have been identified and analysed. Among them are the following ones: military, strategic, economic, political, nuclear, messianic, personal, factor of external threat («image of enemy »), geopolitical. The medium and long-term goals of the USA foreign policy strategy in Eurasia have been identified. The system analysis of the factors, goals and geopolitical concepts used by the White House in realising its foreign policy, both during the Cold War and in its aftermath, allows tracing how did the liberal paradigm, which foundations had been formed within the historical events of the first post-war years, become a reality today. The article demonstrates that the expansion of the new world order paradigm is being accompanied by permanent economic, geopolitical and military expansion of the United States. In the framework of that expansion the territories of modern Belarus, Russia and other states of the former USSR are the stepping stones necessary to gain world leadership. From this point of view, the Cold War is not over. Yet its forms and methods have changed. Therefore, the new world order appears as being a multifaceted phenomenon projected into the informational, economic, and military-political dimensions to establish the global power of the USA in the world and that of the forces that stand behind it. It is concluded that the obeyance of the national spirit to the interests of the US foreign policy strategy is the main conceptual goal of the latter. This fact determines the nature of the modern war on consciousness. Understanding the new world order phenomenon as well as the USA foreign policy strategy as being the instrument of its establishing is necessary to ensure national security and successive development of the Belarusian state.
Keywords: USA; foreign policy strategy; factors; formation; implementation; ideology; globalism; new world order; national security; continuity